Investigation of the dose and structure effects of lipid oxidation products aldehydes on the generation of heterocyclic amines: A case study of 2-amino-1-methyl-6-phenylimidazo [4,5-b] pyridine (PhIP) - Mantong Zhao; Zhongyuan Liu; Mengyin Zha; Ying Sun; Haohao Shi; Xueying Zhang; Chuan Li; Guanghua Xia (Food Chemistry: X)
The effect of aldehydes from lipid oxidation on the generation of heterocyclic amine 2-amino-1-methyl-6-phenylimidazo [4,5-b] pyridine (PhIP) during pan-frying of golden pompano fillets was investigated. It was observed the aldehydes that contribute to thiobarbituric acid reactive substances (TBARS) value significantly promoted PhIP generation (p < 0.05). The defat treatment of fresh fish tissue significantly reduced the PhIP formation in pan-fried products (p < 0.05). During pan-frying, massive aldehydes were generated in a time-dependent manner with acrolein, propanal, hexanal, 4-hydroxy-nonenal (HNE), and 2,4-decadienal (DDE) as the abundant species. In the established chemical model, these aldehydes congruously promoted PhIP formation with the increased concentration, especially acrolein, HNE and DDE. Therefore, aldehydes could significantly enhance the PhIP generation under processing. However, except for propanal and hexanal, the promoting effect was slightly decreased with high levels of aldehydes addition due to the strong electrophilic properties and participation of reaction with the amino group of phenylacetaldehyde, creatinine, even PhIP.